2009
DOI: 10.1111/j.1753-4887.1996.tb03851.x
|View full text |Cite
|
Sign up to set email alerts
|

Folate, Vitamin B12, and Neuropsychiatric Disorders

Abstract: Folate and vitamin B,, are required both in the methylation of homocysteine to methionine and in the synthesis of S-adenosylmethionine. S-adenosylmethionine is involved in numerous methylation reactions involving proteins, phospholipids, DNA, and neurotransmitter metabolism. Both folate and vitamin B,, deficiency may cause similar neurologic and psychiatric disturbances including depression, dementia, and a demyelinating myelopathy. A current theory proposes that a defect in methylation processes is central to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
103
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(108 citation statements)
references
References 45 publications
2
103
1
2
Order By: Relevance
“…On the other hand, B-vitamins and folate are involved in serotonin and other monoamine neurotransmitters synthesis and other methylation reactions, for example, homocysteine catabolism (Bottiglieri, 1996). Another factor that can be taken into account to explain our findings is the educational or social level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, B-vitamins and folate are involved in serotonin and other monoamine neurotransmitters synthesis and other methylation reactions, for example, homocysteine catabolism (Bottiglieri, 1996). Another factor that can be taken into account to explain our findings is the educational or social level.…”
Section: Discussionmentioning
confidence: 99%
“…Other nutrients which are altered in patients with major depression and that can influence neurotransmitter production include tryptophan (and other large neutral amino acids: valine, leucine, isoleucine, phenylalanine and tyrosine) (Maes et al, 2011c, Markus, 2008, Toker et al, 2010, folic acid (Miller, 2008, Stahl, 2008, zinc , Szewczyk et al, 2011, vitamin B12 (Bottiglieri, 1996, Deana et al, 1977), vitamin B6 (Calderon-Guzman et al, 2004, Demisch and Kaczmarczyk, 1991, Hartvig et al, 1995 and iron (Baumgartner et al, 2012, Burhans et al, 2005, Coe et al, 2009). Omega-3 EFAs are also able to modify monoaminergic neurotransmission (Chalon, 2006, Su, 2009).…”
Section: Diet and Its Effect On Neurotransmittersmentioning
confidence: 99%
“…Negative associations between folate and vitamin B 12 at baseline and homocysteine 18 months later reflect the causal relationship of folate and vitamin B 12 with levels of homocysteine (3) . Our cross-sectional analyses suggest that folate contributes more to homocysteine than vitamin B 12 , consistent with previous reports (60) .…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is an amino acid that, at high levels, is associated with adverse health outcomes such as CVD (5) and depression (6) ; SAMe is a methyl donor with potential antidepressant properties due to its involvement in the metabolism of neurotransmitters such as norepinephrine, dopamine, melatonin and serotonin (7) . Functional deficiencies of folate or vitamin B 12 may, therefore, potentially result in disturbed mood either directly or indirectly via elevated homocysteine (3) and reduced SAMe concentrations (8) . Cross-sectional studies have found an association between depression and concentrations of folate (1,9) , vitamin B 12 (10,11) and homocysteine (12,13) .…”
mentioning
confidence: 99%
See 1 more Smart Citation